Bibliometric analysis on dividend studies in Brazil (Research, Society and Development, 2020)
The aim of this study was to map the theories regarding the distribution of dividends in the Brazilian capital market. Based on an analysis carried out directly in the journals listed in the Qualis/CAPES A2 and B1 (Quadrennium 2013-2016), published articles between 2008 and 2019. In total, 252 articles were analyzed, from which the theories were most frequently extracted regarding the thematic, as well as the contributions of the studies, through an individualized analysis by published article. In view of this, the sample was reduced to 34 articles, which presented 9 different theories, with 85 authors and 27 educational institutions. After the presentation of each theory found, the results found are discussed, and were possible to confirm the presence of some theories in the national context. As a contribution, this research clarifies the most used theories on dividends, who are the Brazilian authors with the largest number of publications, their respective citations and impact of their papers.